An easy synthesis of 5-functionally substituted ethyl 4-amino-1-aryl- pyrazolo-3-carboxylates: interesting precursors to sildenafil analogues - Ghozlan, Said A S (Beilstein-Institut, 2007)
3-Oxo-2-arylhydrazononitriles 1a-c react readily with chloroacetonitrile, ethyl chloroacetate, and with phenacyl chloride to give 4-aminopyrazoles 4a-e. The pyrazolo[4,3-d]pyrimidine derivatives 7 and 10 are synthesized via reaction of the aminopyrazole 4b with phenylisothiocyanate and DMFDMA/NH(4)OAc respectively.